Formulasi dan Evaluasi Mutu Fisik Sirup Sari Buah Jeruk Nipis (Citrus Aurantifolia) sebagai Antioksidan Alami: Formulation and Evaluation of Physical Quality of Lime Juice Syrup (Citrus Aurantifolia) as a Natural Antioxidant - Diah Ayu Kumala Sari; Anasthasia Pujiastuti (Journal of Holistics and Health Sciences, 2024)
Lime fruit (Citrus aurantifolia) contains essential oils, saponins, flavonoids and vitamin C. Lime juice can be made into antioxidant syrup preparations because it contains flavonoids and vitamin C. The purpose of this study was to make lime juice syrup with physical quality that meets the requirements and analyze the IC50 value of the preparation. The syrup preparation was made using a mixing method with variations in lime juice concentration, namely 25% v/v, 30% v/v and 35% v/v. The evaluations conducted included organoleptic, homogeneity, pH, viscosity, specific gravity and antioxidant activity using the DPPH method with vitamin C as a comparator. The research data were analyzed statistically using one way Anova and Least Significant Difference (LSD) with SPSS version 26. The results of the physical quality evaluation of the syrup preparation were liquid, light yellow in color, had a distinctive lime odor, tasted sour to sweet, homogeneous, pH 4.03-4.50, viscosity 37.60-45.88 cPs, and specific gravity 1.247-1.260. The IC50 value of Vitamin C was 11.04 ppm, lime juice 21.54 ppm, syrup preparation 33.96 - 46.54 ppm. Lime juice syrup (Citrus aurantifolia) that produces the best physical quality is formula 3 with an active substance concentration of 35% v/v, based on organoleptic, homogeneity, pH, specific gravity, and viscosity meet the requirements. The IC50 value of F1 syrup (25% v/v) is 46.54 ppm, F2 (30% v/v) is 41.48 ppm, and F3 (35% v/v) is 33.96 ppm, including the very strong category. ABSTRAK Buah jeruk nipis (Citrus aurantifolia) mengandung minyak atsiri, saponin, flavonoid dan vitamin C. Sari buah jeruk nipis dapat dibuat sediaan sirup antioksidan karena mengandung flavonoid dan vitamin C. Tujuan penelitian ini yaitu membuat sirup sari buah jeruk nipis dengan mutu fisik yang memenuhi syarat dan menganalisis nilai IC50 sediaan. Sediaan sirup dibuat menggunakan metode pencampuran dengan variasi konsentrasi sari buah jeruk nipis yaitu 25%v/v, 30%v/v dan 35%v/v. Evaluasi yang dilakukan meliputi organoleptis, homogenitas, pH, viskositas, bobot jenis dan aktivitas antioksidan menggunakan metode DPPH dengan pembanding vitamin C. Data penelitian di analisis statistik menggunakan one way Anova dan Least Significant Difference (LSD) dengan SPSS versi 26. Hasil evaluasi mutu fisik sediaan sirup berbentuk cair, berwarna kuning muda, berbau khas jeruk nipis, berasa asam hingga manis, homogen, pH 4,03-4,50, viskositas 37,60-45,88 cPs, dan bobot jenis 1,247-1,260. Nilai IC50 Vitamin C 11,04 ppm, sari buah jeruk nipis 21,54 ppm, sediaan sirup 33,96 - 46,54 ppm. Sirup sari buah jeruk nipis (Citrus aurantifolia) yang menghasilkan mutu fisik paling baik yaitu formula 3 dengan konsentrasi zat aktif 35%v/v, berdasarkan organoleptis, homogenitas, pH, bobot jenis, dan viskositas memenuhi syarat. Nilai IC50 pada sirup F1 (25%v/v) sebesar 46,54 ppm, F2 (30%v/v) sebesar 41,48 ppm, dan F3 (35%v/v) sebesar 33,96 ppm termasuk kategori sangat kuat.